2020
DOI: 10.1002/open.202000173
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Conjugates of Non‐steroidal Anti‐Inflammatory Drugs: Synthesis, Structures, Anti‐proliferative Assays, Computational Docking, and Inflammatory Response

Abstract: In an effort to combine the anti‐proliferative effect of CUR‐BF2 and CUR compounds with anti‐inflammatory benefits of non‐steroidal anti‐inflammatory drugs (NSAIDs), a library of the bis‐ and mono‐NSAID/CUR‐BF2 and NSAID/CUR conjugates were synthesized by coupling flufenamic acid, flurbiprofen, naproxen, indomethacin, and ibuprofen to diversely substituted hydroxy‐benzaldehydes via an ester linkage, and by subsequent reaction with acetylacetone‐BF2 to form the bis‐ and the mono‐NSAID/CUR‐BF2 adducts. Since con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
(122 reference statements)
1
12
0
Order By: Relevance
“…It may be attributed to the purification step even though the purification step has been optimized in terms of the mobile and stationary phases. Besides, the TLC result showed that the reaction was not completed after 24 h, similar to the work reported by Laali and colleagues [ 40 ]. The MPA-CUR conjugate product was found as yellow solid after purification using C18-bonded silica as the stationary phase and methanol: water (8:2) as the mobile phase.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…It may be attributed to the purification step even though the purification step has been optimized in terms of the mobile and stationary phases. Besides, the TLC result showed that the reaction was not completed after 24 h, similar to the work reported by Laali and colleagues [ 40 ]. The MPA-CUR conjugate product was found as yellow solid after purification using C18-bonded silica as the stationary phase and methanol: water (8:2) as the mobile phase.…”
Section: Resultssupporting
confidence: 88%
“…EDC was selected because the unreacted EDC can be easily removed from the reaction by partitioning with water due to its good water solubility [ 39 ]. Several organic solvents, including DCM and DMF ( N , N -dimethylformamide), are commonly used in the Steglich esterification method [ 37 , 38 , 40 , 41 ]. Due to the low solubility of curcumin in DCM, a large volume of DCM used to dissolve CUR resulted in a very diluting reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin is a documented antiproliferative and antiangeonic as well as a cure for Alzheimer's disease, cardiac, diabetes, and so forth. [ 1–9 ] Curcumin exists in two tautomeric structures i.e., keto and enol form. The enol form of the curcumin is more stable in solid as well as in the solution phase and is able to penetrate the blood–brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature, it is explained that the more negative energy for the formation of the complex between small molecule and receptor, the more will be the stability or interaction. [ 4,5,9,11,14,19,22–24 ]…”
Section: Introductionmentioning
confidence: 99%